2004
DOI: 10.1080/00207450490509113
|View full text |Cite
|
Sign up to set email alerts
|

Brief Communication: EFFECTS OF EXTERNAL QI-THERAPY ON EMOTIONS, ELECTROENCEPHALOGRAMS, AND PLASMA CORTISOL

Abstract: The authors investigated the effect of external Qi-therapy (EQT) on changes in encephalograms (EEGs) and circulating cortisol concentrations. Ten college students participated in crossover sessions, receiving EQT or placebo treatment with their eyes open. Subjects reported improved emotions of satisfaction, relaxation, and calmness during EQT as compared to levels reported during placebo treatments. There were significant differences in the proportions of alpha and beta EEG waves between the two sessions, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…OPT originated in Japan for the promotion of good health. OPT is similar to EQT, [2][3][4][5] Reiki, 6 and Johrei 8,9 in that it appears to enhance patient health using bioenergy or qi. In OPT, a practitioner treats a patient using a modality that emits bioenergy, or qi through the practitioner's palm, without physically touching the patient.…”
Section: Biofield Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…OPT originated in Japan for the promotion of good health. OPT is similar to EQT, [2][3][4][5] Reiki, 6 and Johrei 8,9 in that it appears to enhance patient health using bioenergy or qi. In OPT, a practitioner treats a patient using a modality that emits bioenergy, or qi through the practitioner's palm, without physically touching the patient.…”
Section: Biofield Therapymentioning
confidence: 99%
“…One (1) study evaluated differences in a and bwaves and plasma cortisol between EQT and control (placebo) sessions. 2 However, this study only analyzed the EEG for a 3-minute period of EQT, and changes in longer treatment periods were not investigated. Maltez et al 13 reported that recordings over short time periods significantly biased the estimation of the EEG parameters.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While not solely, or even strictly, Daoist, 16 studies of qigong phenomena may inform psychological researchers regarding concepts common to Daoism (e.g., qi). One of the major contributors to the study of qigong practices is Myeong Soo Lee and his colleagues (Lee et al, 2001;Lee, Kang, Lim, & Lee, 2004;Lee, Rim, & Kang, 2004). While primarily involved in the study of the physiological effects of various qi practices, Lee has conducted several studies that included psychological variables.…”
Section: Empirical Studiesmentioning
confidence: 99%